2021
DOI: 10.1089/gtmb.2020.0143
|View full text |Cite
|
Sign up to set email alerts
|

Association of Transforming Growth Factor β1 Gene Polymorphisms and Inflammatory Factor Levels with Susceptibility to Sepsis

Abstract: To study the association of transforming growth factor b1 (TGF-b1) gene single nucleotide polymorphisms (SNPs) and plasma TGF-b1 levels with susceptibility to sepsis. Methods: The genotypes of the TGF-b1 gene rs1800469, rs1800468, rs1800470, and rs1800471 loci in 285 sepsis patients (119 patients with severe sepsis and 166 patients with mild sepsis) and 285 healthy individuals (control group) were analyzed through Sanger sequencing. Enzyme-linked immunosorbent assay was used to detect the levels of plasma infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…A study carried out in China in patients with sepsis associated the rs1800469 polymorphism of the TGF-β1 gene to lower plasma levels of this cytokine and a reduced risk of susceptibility to sepsis. However, the same study observed that the rs1800468 polymorphism was associated with higher levels of TGF-β1 and greater susceptibility to sepsis (ZHENG, et al 2021), a result that is different from the result found in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study carried out in China in patients with sepsis associated the rs1800469 polymorphism of the TGF-β1 gene to lower plasma levels of this cytokine and a reduced risk of susceptibility to sepsis. However, the same study observed that the rs1800468 polymorphism was associated with higher levels of TGF-β1 and greater susceptibility to sepsis (ZHENG, et al 2021), a result that is different from the result found in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…in the lungs, which can release TGF-β1 into the blood of patients (Ghazavi et al, 2020). Zheng et al, in a study carried out in China with 285 patients with sepsis (119 patients with severe sepsis and 166 patients with mild sepsis) and 285 healthy individuals (control group) found plasma levels of TGF-β1 higher in patients with severe sepsis, indicating that the higher concentration of this cytokine contributes to the worsening of the condition (Zheng, Fu & Zhao, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nabrdalik et al [ 32 ], showed that the minor C allele of rs1800471 was associated with the occurrence of chronic kidney disease, whereas the rs1800471 G allele was associated with the presence of hypertension [ 32 ]. Our results are consistent with previous studies that found an association between rs1800471 C > G and higher TGF-β1 levels and susceptibility to sepsis [ 33 ]. Consistent with these results, CTS patients carrying the minor C allele rs1800471 as either homozygotes CC or heterozygotes CG showed a significant increase in serum TGF-β1 levels compared with GG carriers.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have investigated the association of TGF1β-SNPs with various diseases [ 32 , 33 , 34 ], but these SNPs have not yet been studied in CTS patients. We hypothesized that the increase in serum TGF-β1 in CTS patients might be due to genetic variants.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis-induced ARDS patients displayed FASLG−FAS, which reportedly is related to increased protein permeability in the pulmonary alveoli [ 27 ], and CCL3/4/5−CCR1, which is related to the chemokines and proinflammatory cytokines that participate in and promote inflammatory responses related to macrophages [ 28 , 29 ]. Sepsis-only patients displayed IL1B−IL1RAP, of which Interleukin-1-B (IL1B) is a proinflammatory cytokine that plays an important role in sepsis and affects the p38 MAPK and NF κ B signaling pathways [ 30 , 31 ], and TGFB1−TGFBR1, of which transforming growth factor beta1 (TGF-beta1) gene single-nucleotide polymorphisms and plasma TGF-beta1 levels were thought to be associated with susceptibility to sepsis [ 32 ]. Furthermore, we analyzed the downstream TFs targeted by LR pairs ( Figure 3(c) ) and found that different TFs, including SMAD3, RBPJ, and MAX, were targeted in sepsis-only patients, while FOS, STAT3, STAT2, and RB1 were targeted in sepsis-induced patients.…”
Section: Resultsmentioning
confidence: 99%